Characterization of drinking water qualtiy (Biological and Chemical Contaminations) for Sabah kampong community - Carolyn Payus; Farrah Anis F. Adnan; Siti Aishah Mohd Ali; Rohana Tair (Universiti Malaysia Sabah, 2015)
Most part of village at kampong in Sabah has no water supply provided for their need sometimes maybe there Is a water supply facility such as Kudat are, Kota Belud, Kota M~udu and Nabawan, but however there is no water flowing from the tap forcing them to take their water supply alternative such as well water and gravity water. The objective of this research is to assess the chemical and biological characterization of drinking water from well water and gravity water and also to investigate the compliance of the quality of drinking water with Malaysian standard. Four villages were selected which is Kampung Kokol, Inanam. Kampung Bogian, Tambunan, Kampung Kuala Abal, Kota Belud and Kampung Bayag, Kiulu. Based on the heavy metal analysis in Kampung Kokol, Crhromium and zinc obey the standard guidelines with the highest concentration 0.019±0.014 mg/L and 0.070±0.022 mg/L respectively. The sequence concentrations of heavy metals in Kampung Bogian found in harvested rain water were Zn >Cr >Pb and all the heavy metal are below the standard guidelines. For heavy metal analysis in Kampung Kuala Abai shows the highest concentration of magnesium, manganese and copper are 52.66 ± 2.75 mg/L, 0.225 ± 0.053 mg/L and 0.1554 ± 0.0234 mg/L respectively, at which indicates that Mg and Cu obey the standard guideline but not for Mn. Kampung Bayag analysed four heavy metal that is lead, cadmium, zinc and chromium at which show the highest concentration for unboiled gravity water are 0.0229 mg/L, 0.0013 mg/L, 1.2641 mg/L and 0.0040 mg/L respectively at which all the metals below the standard except lead. Boiled gravity water in Kampung Bayag shows the highest heavy metal concentration of lead, zinc and chromium is 0.0087 mg/L, 0.846 mg/L and 0.0028 mg/L respectively at which all obey the standard guideline and also cadmium concentration in boiled gravity water cannot be detected by ICO-OES. For nutrient analysis In Kampung Kokol, both phosphate and nitrate have concentration 0.44±0.11 mg/L and 0.80±0.14 mg/L respectively and obey the standard guidelines. For analYSis nutrient in Kampung Bogian show the concentration of nitrate and sulphate is 2.33±1.52 mg/L and 0.91±0.46 mg/L respectively and below the standard guideline. For analysis nutrient in Kampung Kuala Abai, nitrate, sulphate and chloride is 1.0 ± 0,41 mg/L, 9 ± 9.27 mg/L and 33.84 ± 28.72 mg/L respectively and all are within the standard guidelines. For microbiological analysis in Kampung Kokol shows the total coliform fluctuate from 109±8 CFU/100 mL to 47±8 CFU/lOO mL, meanwhile E.Coli counted is from 100±4 CFU/100 mL to 4±2 CFU/100 mL and both are exceeding the guideline. In kampung Bogian, total coliform in unboiled rain water from 10±14.1 CFU to 132±8.5CFU /100 mL and E.Coli counted is from 0.S±0.7CFU to 58±2.8CFU and both exceeding the guidelines. For boiled rainwater in Kampung Bogian show the total coliform counted from 0 to 46±41.0CFU and E.Colicounted from O±O.O to 20.S±6.3 CFU and majority all the station is still not comply with guidelines. In kampong Kuala Abai, the total coliform and E.Coli counted in well water is from 17 ± 2.12 CFU/100mL to 400 ± 15.56 CFU/100mL and 0 ± 0.00 CFU/100mL to 12 ± 0.00 CFU/I00mL respectively at which both below the standard guidelines of National Drinking Water Quality Standard 2010 for raw water (5,000 CFU/100mL). The analYSis of microbiology parameter in Kampung Bayag show the total coliform and faecal coliform in unboiled gravity water is 30.5 CFU/100mL to 283.5 CFU/100mL and 15.5 CFU/100mL to 92 CFU/100mL respectively at which both exceeding WHO and Food Act 1983 guidelines. For boiled gravity water the total coliform and faecal coliform counted is from 0 CFU/100mL to 129.5 CFU/lOOmL and 0 CFU/100mL to 92 CFU/lOOmL respectively at which only two stations comply with WHO and Food Act 1983 guidelines. Therefore, there should be proper treatment for this alternative water supply so that it can achieve safe drinking water level and can be consume by people especially people in rural areas that not have complete access to clean water facility.